Warrant, Conclusive Reason, and Failure-Of-Transfer-Of-Warrant - Ramachandran, Murali (Problemos, 2018)
[full article, abstract in English; abstract in Lithuanian] Fred Dretske motivates his denial of epistemic closure by way of the thought that the warrant for the premises of a valid argument need not transfer (or ‘transmit’) to the argument’s conclusion. The failure-of-transfer-of-warrant (FTW) strategy has also been used by advocates of epistemic closure as a foil to Michael McKinsey’s argument against the compatibility of first person authority and semantic externalism, and also to illuminate, more generally, why certain valid arguments appear ill-suited for the purpose of establishing their conclusions. This paper takes re-examines some of the central attempts to explain transmission-failure, and a central line of objection to the strategy from Begging-the-Question theorists. The ultimate goal of this paper is to promote a decidedly Dretskean explanation of the unpersuasiveness of the said arguments.